Fomitiporia neotropica, a new species from South America evidenced by multilocus phylogenetic analyses - de Campos Santana, Marisa (2014)
During the revision of the Neotropical Fomitiporia species with resupinate basidiomata, several collections from southern Brazil, central Argentina, and French Guiana were found to represent an undescribed species, on the basis of molecular (DNA sequence) and additional morphological and distributional data. This taxon is described and illustrated as Fomitiporia neotropica sp. nov. The species belongs to the Fomitiporia langloisii lineage, the lineage type within Fomitiporia that so far contains only species with resupinate basidiomata spanning exclusively over the Neotropics. Fomitiporia neotropica is morphologically variable regarding the presence/absence of hymenial setae, and secondarily, regarding the pore size. It also inhabits distinct ecosystems characterized by variable moisture regimes. The range of divergent positions in the DNA sequences used in this study (ITS, 28S, partial tef1-α, and rpb2), between specimens from distant origins, are of the same magnitude as those between specimens of other related species, such as F. langloisii , F. dryophila , F. maxonii, or F. mediterranea. A key to the species from the F. langloisii lineage is given.